Study of structure-dependent chromatographic behavior of glycopeptides using reversed phase nanoLC - Kozlik, Petr; Goldman, Radoslav; Sanda, Miloslav (Electrophoresis, 2017)
Analysis of glycosylation is challenging due to micro- and macro-heterogeneity of the protein attachment. A combination of LC with MS/MS is one of the most powerful tools for glycopeptide analysis. In this work, we show the effect of various monosaccharide units on the retention time of glycopeptides. Retention behavior of several glycoforms of six peptides obtained from tryptic digest of haptoglobin, hemopexin, and sex hormone-binding globulin was studied on a reversed phase chromatographic column. We observed reduction of the retention time with increasing number of monosaccharide units of glycans attached to the same peptide backbone. Fucosylation of larger glycans provides less significant retention time shift than for smaller ones. Retention times of glycopeptides were expressed as relative retention times. These relative retention times were used for calculation of upper and lower limits of glycopeptide retention time windows under the reversed phase conditions. We then demonstrated on the case of a glycopeptide of haptoglobin that the predicted retention time window boosts confidence of identification and minimizes false-positive identification. Relative retention time, as a qualitative parameter, is expected to improve LC-MS/MS characterization of glycopeptides.
Keywords: glykopeptidy; proteomika; nanotechnologie; LC-MS/MS; chromatografie s reverzní fází; Sensitivity and Specificity; Chromatography, Reverse-Phase; Glycoproteomics; Reversed phase chromatography; Nanotechnology; glykosylace; trypsin; Peptide Fragments; Trypsin; Proteomics; Glycosylation; Humans; peptidové fragmenty; senzitivita a specificita; Glycopeptide chromatography; Glycopeptides; Glycoform-dependent retention prediction; lidé